Pengaruh Gaya Kepemimpinan Terhadap Kinerja Pegawai dengan Motivasi dan Disiplin Kerja Sebagai Variabel Intervening Pada Dinas Pekerjaan Umum dan Perumahan Rakyat Provinsi Jambi - Pantun Bukit; Fakhrul Rozi Yamali; Rizki Ananda; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2019)
The purpose of this research is to obtain an overview of the leadership style, motivation, discipline, and performance of employees in the Office of Public Works and people's housing of Jambi province; And to know the influence of leadership styles on motivation, work discipline and performance; And to know the influence of leadership styles through motivation and work discipline toward performance. The population in this study was the Office of Public Works and people's housing of Jambi province, amounting to 286 employees. The size or number of samples in this study was determined based on the theory that Slovin developed with a margin error of 5% obtained as many as 75 people. Analytical techniques using the analysis path, are transmitted by testing R Square and partial and simultaneous hypothesis testing with T-Test and F-Test. Testing path of analysis carried out, obtained the results of the leadership style has an influence on the motivation, work discipline and performance of employees, motivation and work discipline also has an influence on both the performance and Simultaneously, and the leadership style has an influence on performance through motivation and work discipline. This explains that if an organization has a leader with a leadership style that is appropriate for its employees, this will affect the motivation, work discipline, and performance of its employees. Because the right leadership style has a very dominant role in determining the success of an organization, the right leadership style will be able to direct its employees to work optimally in achieving organizational objectives.